Sediment nitrogen contents controlled by microbial community in a eutrophic tributary in Three Gorges Reservoir, China. (1st December 2022) - Lv, Kun; Guo, Xiaojuan; Wang, Congfeng; Su, Qingqing; Liu, Defu; Xiao, Shangbin; Yang, Zhengjian
Abstract: Nitrogen pollution caused serious environmental problems in reservoir ecosystems. Reducing nitrogen pollution by enhancing nitrogen removal in river sediments deserved intensive research. Distributions of nitrogen contents in sediment-water interface were characterized along the Xiangxi bay (XXB), a eutrophic tributary in Three Gorges Reservoir, China. More than 47% of total Kjeldahl nitrogen (TKN) and 67% of total organic nitrogen (TON) were degraded during burial. Higher TN, TON and NH4 + consuming at downstream sites indicated stronger nitrogen mineralization and release due to higher turbulence of the overlying density currents. Nitrifying bacteria, denitrifying bacteria, anaerobic ammonium oxidizing (anammox) bacteria and nitrite/nitrate-dependent anaerobic methane oxidation (N-DAMO) bacteria were detected in nitrate-ammonium transition zone. Nitrogen contents transitions were responded to microbial stakeholders indicated microbially mediated nitrogen cycling in sediments. The dissolved oxygen and nitrate availabilities were the key limits of denitrification and associated reactions. These results suggested microbial mediated nitrogen cycling processes in sediments were critical for nitrogen removal in aquatic ecosystems, and replenishing dissolved oxygen and nitrate was expected to enhance sediment denitrification and strengthen potential environmental self-purification. Graphical abstract: Image 1 Highlights: Nitrogen contents varied strongly in a eutrophic tributary's sediments in the TGR. Sediment nitrogen contents highly responded to functional composition of microbial community. Significant nitrogen transition indicated effectively nitrogen removal in sediments. Oxygen and nitrate availabilities were the key limits of nitrogen removal in the sediments.